Left ventricular myocardial mass determination by contrast enhanced colour Doppler compared with magnetic resonance imaging. Issue 1 (16th December 2004) - Bezante, G P; Chen, X; Molinari, G; Valbusa, A; Deferrari, L; Sebastiani, V; Yokoyama, N; Steinmetz, S; Barsotti, A; Schwarz, K Q
Abstract : Objective: To assess the feasibility of using contrast enhanced colour Doppler echocardiography to determine left ventricular (LV) mass and to compare its accuracy with LV mass obtained by magnetic resonance imaging (MRI). Methods: Images were acquired in the short axis plane of the heart, derived from coronal and sagittal scout views and double oblique angulation. The LV mass was calculated by two methods: Simpson's rule and the area–length method. Levovist (Schering AG, Berlin, Germany) 2.5 g was given by slow intravenous bolus or infusion over about 45 seconds for contrast imaging. LV images were captured in the apical two chamber, four chamber, and three chamber views. Each contrast harmonic colour Doppler image was converted to a cavity-only image by simple image mathematics. Results: 27 (77.1%) of the patients (mean (SD) age 66.2 (8.9) years) were men. There was a mean (SD) interval of 6.6 (8.6) days (range 0–27 days) between echocardiography and MRI. The mean (SD) LV mass determined by MRI Simpson's rule method was 171.0 (52.4) g (range 105.1–318.7 g). The mean LV mass (SD) determined by the echocardiographic Simpson's rule method was 178.2 (47.0) g (range 112.6–307.6 g). The mean (SD) MRI area–length LV mass was 187.3 (64.5) g (range 109.0–393.6 g). The linear regression correlation between LV mass determined by MRI Simpson's and echocardiographic Simpson's methods was excellent (y = 1.022x, R 2 = 0.986) with a mean (SD) difference of 7.20 (20.9) g. The linear regression correlation between the MRI area–length LV mass and MRI Simpson's LV mass was excellent (y = 1.101x, R 2 = 0.989) with a mean (SD) difference of 16.3 (22.3) g. Conclusions: LV mass may be obtained reliably by contrast enhanced colour Doppler and two dimensional echocardiography. The contrast Doppler method accurately determines LV mass with excellent agreement with the MRI technique.